Financial Feasibility Analysis of Durian Fruit Business (Durio Zibethinus ) - Afrina Hidayatul Arifah; Mazidatul Faizah (AGARICUS: Advances Agriculture Science & Farming, 2022)
A number of tourist areas in Wonosalam District, Jombang Regency, are the main attraction for tourists. One of the attractions of Wonosalam District is the durian fruit. For durian lovers, Wonosalam is familiar to the ears, so that when harvest time arrives, they will enjoy the fruit as well as travel to enjoy its natural beauty. In Wonosalam there are various types of durian. Starting from Durian Montong, Musang King, to Wonosalam's mainstay, Durian Bido. For the price of Durian Bido, it starts from Rp. 50,000 to Rp. 200,000/seed depending on the type and weight of the fruit. Research Objectives (1). Knowing the income level of durian farming in Sumber Village, Kec. Wonosalam, (2). Knowing the financial feasibility of durian farming in Sumber Village, Kec. Wonosalam in terms of B/C ratio. This research was conducted in Sumber Hamlet, Wonosalam Village, Wonosalam District, Jombang Regency. The location of this research was chosen intentionally (purposive sampling) because, in Sumber Hamlet, Wonosalam Village, Wonosalam District, there are 32 residents who have land planted with durian trees with an area of ​​<5000 m2, so the respondents who were taken in this study were only 4 people. . With the consideration of these 4 people, the land area is > 5000 m2. (1). The total cost of the durian fruit farming analysis on average is Rp. 62,109,925/Ha/Year, the average durian fruit farming revenue is Rp. 64,175,000/Ha/Year, and the average income earned by farmers is Rp. 90,181,575/Ha/Year. (2). R/C Ratio of 2.4. (3). B/C Ratio of 1.4. In Sumber Hamlet, Wonosalam Village, Wonosalam District, there are 32 residents who have land planted with durian trees with an area of ​​<5000 m2, so the respondents who were taken in this study were only 4 people. With the consideration of these 4 people, the land area is > 5000 m2. (1). The total cost of the durian fruit farming analysis on average is Rp. 62,109,925/Ha/Year, the average durian fruit farming revenue is Rp. 64,175,000/Ha/Year, and the average income earned by farmers is Rp. 90,181,575/Ha/Year. (2). R/C Ratio of 2.4. (3). B/C Ratio of 1.4. In Sumber Hamlet, Wonosalam Village, Wonosalam District, there are 32 residents who have land planted with durian trees with an area of ​​<5000 m2, so the respondents who were taken in this study were only 4 people. With the consideration of these 4 people, the land area is > 5000 m2. (1). The total cost of the durian fruit farming analysis on average is Rp. 62,109,925/Ha/Year, the average durian fruit farming revenue is Rp. 64,175,000/Ha/Year, and the average income earned by farmers is Rp. 90,181,575/Ha/Year. (2). R/C Ratio of 2.4. (3). B/C Ratio of 1.4. With the consideration of these 4 people, the land area is > 5000 m2. (1). The total cost of the durian fruit farming analysis on average is Rp. 62,109,925/Ha/Year, the average durian fruit farming revenue is Rp. 64,175,000/Ha/Year, and the average income earned by farmers is Rp. 90,181,575/Ha/Year. (2). R/C Ratio of 2.4. (3). B/C Ratio of 1.4. With the consideration of these 4 people, the land area is > 5000 m2. (1). The total cost of the durian fruit farming analysis on average is Rp. 62,109,925/Ha/Year, the average durian fruit farming revenue is Rp. 64,175,000/Ha/Year, and the average income earned by farmers is Rp. 90,181,575/Ha/Year. (2). R/C Ratio of 2.4. (3). B/C Ratio of 1.4.